2015
DOI: 10.1158/2326-6066.cir-15-0065
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Host Type-I IFN Signaling Accelerates Metastasis and Impairs NK-cell Antitumor Function in Multiple Models of Breast Cancer

Abstract: Metastatic progression is the major cause of breast cancerrelated mortality. By examining multiple syngeneic preclinical breast cancer models in mice lacking a functional type-I interferon receptor (Ifnar1 À/À mice), we show that host-derived type-I interferon (IFN) signaling is a critical determinant of metastatic spread that is independent of primary tumor growth. In particular, we show that bone metastasis can be accelerated in Balb/c Ifnar1 À/À mice bearing either 4T1 or 66cl4 orthotopic tumors and, for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…S1 C-G), indicating that phosphorylation of eIF4E was dispensable for normal hematopoiesis. In the context of 66cl4 mammary tumors, previous studies have found neutrophils, natural killer (NK) cells, and the ratio of CD8 + T cells to T regulatory (CD8 + /T reg ) cells to be important for metastasis (20)(21)(22). However, analysis of dissociated primary mammary tumors indicated that the CD8 + /T reg ratio was the same in WT and eIF4E S209A mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…S1 C-G), indicating that phosphorylation of eIF4E was dispensable for normal hematopoiesis. In the context of 66cl4 mammary tumors, previous studies have found neutrophils, natural killer (NK) cells, and the ratio of CD8 + T cells to T regulatory (CD8 + /T reg ) cells to be important for metastasis (20)(21)(22). However, analysis of dissociated primary mammary tumors indicated that the CD8 + /T reg ratio was the same in WT and eIF4E S209A mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Tumor cell decreases in JAK2 target genes (Socs3, Egfr) were reported, which indicated that target inhibition was achieved, along with decreases in activated STAT3, which was high at trial commencement in all patients. However, significant decreases in GZMB + CD8 + T cells were observed in metastatic lesions compared to primary tumors, suggesting that JAK2 inhibition, which is critical in IFN responses and immune induction, particularly in a metastatic setting [206,207], might abrogate immune-mediated antitumor effects, as others have proposed. The trial was subsequently terminated due to progressive disease in all surviving enrolled patients.…”
Section: Jak Inhibitionmentioning
confidence: 88%
“…In mice lacking IFNAR1, loss of type-1 interferon signaling is sufficient to promote metastasis of breast cancer to lung, independently of the growth of primary tumors (159). Reduced expression of CD69 and IFNγ, two primary biomarkers of Natural Killer (NK) cells, also showed that the homeostasis of the NK population in the immune system which is dependent on signaling through IFNAR1 receptors was impaired in the process (159). The cytokine IL-2 is used as an immunotherapeutic agent to induce anti-metastatic and cytotoxic effects in cancer cells and has been approved for the treatment of metastatic renal cell carcinoma and melanoma.…”
Section: Novel Interactions Of Ifnar1 and Gart May Point At The Influmentioning
confidence: 99%